Waruga as a Unique Cemetery for the Minahasa Tribe - Khairul Tri Anjani; Ponco Setiyonugroho (Criksetra: Jurnal Pendidikan Sejarah, 2023)
This article aims to review the Waruga site and how the Minahasa people carry out burials. The research method used to study Waruga as a burial place for the unique Minahasa tribe is library research. Minahasa is part of Indonesia, in the North Sulawesi region, which has a unique history and culture, one of which is the relics of the Waruga site, which come from the megalithic era. Many Waruga live scattered throughout the Minahasa region, especially in the village of Sawangan, north of Minahasa. The Waruga site is a cultural heritage site protected by the state. Waruga is the last house considered by the Minahasa people as the place where the bodies and souls of their ancestors return to heaven. Waruga is a megalithic tomb spread across Minahasa. Based on archaeological analysis, waruga is a place of worship like a temple where ancestral spirits (gods) reside. Waruga there are several geometricdecorations, plant ornamental patterns, animal ornamental patterns and human ornamental patterns. These ornamental motifs have their own meanings.